DNA Methylation of the Aryl Hydrocarbon Receptor Repressor Associations With Cigarette Smoking and Subclinical Atherosclerosis. (October 2015) - Reynolds, Lindsay M.; Wan, Ma; Ding, Jingzhong; Taylor, Jackson R.; Lohman, Kurt; Su, Dan; Bennett, Brian D.; Porter, Devin K.; Gimple, Ryan; Pittman, Gary S.; Wang, Xuting; Howard, Timothy D.; et al.
Abstract : Background—: Tobacco smoke contains numerous agonists of the aryl hydrocarbon receptor (AhR) pathway, and activation of the AhR pathway was shown to promote atherosclerosis in mice. Intriguingly, cigarette smoking is most strongly and robustly associated with DNA modifications to an AhR pathway gene, the AhR repressor ( AHRR ). We hypothesized that altered AHRR methylation in monocytes, a cell type sensitive to cigarette smoking and involved in atherogenesis, may be a part of the biological link between cigarette smoking and atherosclerosis. Methods and Results—: DNA methylation profiles of AHRR in monocytes (542 CpG sites±150 kb of AHRR, using Illumina 450K array) were integrated with smoking habits and ultrasound-measured carotid plaque scores from 1256 participants of the Multi-Ethnic Study of Atherosclerosis (MESA). Methylation of cg05575921 significantly associated ( P =6.1×10 −134 ) with smoking status (current versus never). Novel associations between cg05575921 methylation and carotid plaque scores ( P =3.1×10 −10 ) were identified, which remained significant in current and former smokers even after adjusting for self-reported smoking habits, urinary cotinine, and well-known cardiovascular disease risk factors. This association replicated in an independent cohort using hepatic DNA (n=141). Functionally, cg05575921 was located in a predicted gene expression regulatory element (enhancer) and had methylation correlated with AHRR mRNA profiles ( P =1.4×10 −17 ) obtained from RNA sequencing conducted on a subset (n=373) of the samples. Conclusions—: These findings suggest that AHRR methylation may be functionally related to AHRR expression in monocytes and represents a potential biomarker of subclinical atherosclerosis in smokers. Abstract : Supplemental Digital Content is available in the text.